Repugnancy And the Incompatibility Clauses and Their Impact on Customary Law: Some Lessons for Cameroon (Zien Journal of Social Sciences and Humanities, 2021)
The repugnancy doctrine was introduced in Cameroon in the 18th Century through received English laws. This doctrine prescribes that the courts shall not enforce any customary law rule if it is contrary to public policy or repugnant to natural justice, equity and good conscience. The doctrine is generally criticised for its use of foreign standards to assess the validity of the customary law rules. This article, however, contends that repugnancy doctrine had played a positive role in the development of customary law in Cameroon by removing it harsh aspects. Most African country repealed the repugnancy provisos when they obtained independence, but Cameroon still retains it. The article makes reference to the position in South African. In the South African context, this article found that the repugnancy proviso had outlived its usefulness and courts now apply customary law subject to the constitution and any legislation that specifically deals with customary law. This position, the article commends for Cameroon